QURANIC EXEGESIS JOURNALISM IN ISLAMIC MAGAZINES IN INDONESIA BETWEEN 1970-1980 (JOURNAL OF INDONESIAN ISLAM, 2023)
The existence of Quranic exegesis journalism is a relatively interesting phenomenon. As media content, the field of tafsir is likely to adapt to media routine practices, social systems, and social institution forces wherein the media is produced. In the period 1970-1980, Indonesia’s economic planning and political system had been deeply committed to developmentalist and modernist in orientation, and required social forces, including media and religious institutions, to promote this national goal. This study aims to explore the influence of journalistic practices in shaping the tafsir of the Quran in three magazines in Indonesia published from 1970 to 1980, namely Ashri Magazine, Panji Masyarakat, and Suara Muhammadiyah. The result of the study illustrates that the tafsir of the Quran within observed Islamic magazines adapted to the logic of journalism. Over the course of the period, Islamic magazines carried out Quranic exegesis journalism by defining issues and discourses of developmentalism and modernity as part of policy and public agendas in order to gain legitimacy from the Indonesian Muslim community. Additionally, this study argues that the journalism of tic Quranic interpretation is one of the study fields of the tafsir of the Quran in Indonesia which is relatively unexplored throughout the ages.